If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1x + 7 = 19 Reorder the terms: 3 + 7 + -1x = 19 Combine like terms: 3 + 7 = 10 10 + -1x = 19 Solving 10 + -1x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 19 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 19 + -10 -1x = 19 + -10 Combine like terms: 19 + -10 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9
| .4w-11=-3 | | 4(5r+45)= | | 2,236,000+(-17.740x)=3,500,000 | | a^2-3ax+2ap-6=0 | | 5(x-3)=2(x-5) | | 11*i=0 | | 6(53+x)=x+2 | | 1/3(x-6)=4x-2/5(2-x) | | 53+x=6(x+2) | | 10+3y=90 | | 5x-19-3=-7 | | 3x=1x-6 | | 2(1+2x)=-6+3x | | 2x+56+4x-2=90 | | -a^2-6a=0 | | 2x+25=90 | | i-3=0 | | 76=y+48 | | 3i-4=0 | | 8x+r= | | -s^2+15s=0 | | 7x-9+5x+3=54 | | -b^2-13b=0 | | 1/5-10=-25 | | -17x+17=119 | | -2w=70 | | 2(2y-1)=3y+10 | | x-2+4x=6x-9 | | x^3-7x^2-2x-40=0 | | 9x-10+4(x-1)=90 | | 7(6x-5)+11x= | | v=0.2a+0.3b |